Understanding African Expatriates’ Conversions to Islam in Bahrain - Harunani, Mohamed Quadir; Ushama, Thameem (Advances in Social Sciences Research Journal, 2025)
This exploratory study looks at the various motivations to explain why Sub-Saharan African expatriate workers are converting to Islam in Bahrain. A quantitative approach was utilized where 294 Africans who recently accepted in this predominantly Muslim country completed a detailed survey. Oneness of God [Tawheed] was the overwhelmingly largest reason for these individuals to switch faith from Christianity to Islam. Additionally, the Islamic concepts of Fitrah [innate disposition] and Hedayah [Divine Guidance] further explain the journeys that these Africans undertook in their search for meaning. The conclusions drawn from the findings of this study emphasize the importance of employing these fundamental Islamic concepts in reaching out not only to the African community in Bahrain but also for inviting [Da’wah] other Christian communities in the Gulf and other parts of the world.